Complementary effect of fibrinogen and rFVIIa on clotting ex vivo in Bernard-Soulier syndrome and combined use during three deliveries. (August 2014) - Palsson, Ragnar; Vidarsson, Brynjar; Gudmundsdottir, Brynja R.; Larsen, Ole H.; Ingerslev, Jorgen; Sorensen, Benny; Onundarson, Pall T.
Abstract Women with Bernard-Soulier syndrome (BSS) are considered to be at high risk of serious bleeding during childbirth. Due to the frequently occurring platelet transfusion refractoriness, alternative prophylactic therapy is required. Using rotational thromboelastometry, we evaluated the whole blood coagulation profile of a pregnant woman with BSS before and after spiking ex vivo with different concentrations of recombinant activated factor VII (rFVIIa) and fibrinogen. As experiments suggested improved clotting with clinically applicable concentrations of both agents in a complementary manner, the findings were confirmed on blood from a non-pregnant woman and three men suffering from BSS. During delivery, bleeding refractory to platelets occurred and immediately following delivery she received both rFVIIa and fibrinogen intravenously. Immediate cessation of bleeding occurred, and no postpartum hemorrhage was seen. Another woman with BSS later also received the same rFVIIa and fibrinogen treatment prophylactically after delivery without any postpartum bleeding. Eventually, the first woman during her second delivery received the same treatment again prophylactically without any bleeding. No side effects were observed during these three deliveries. Our observations suggest that rFVIIa combined with fibrinogen may provide a beneficial clinical hemostatic effect partly by separate but complementary mechanisms.